Media Card Sort dan Couple Card untuk Peningkatan Kemampuan Berpikir Kritis Peserta Didik di Sekolah Dasar - Pangestu, Deviyanti; Kurnia, Elsyah; Lestari, Yulita Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2024)
This study aims to determine the effect and differences in the use of card sort media and couple cards on the critical thinking skills of IPAS students. The method used in this research is quasi experimental with a non-equivalent control group design. The population and sample in this study were obtained through purposive sampling technique with a total sample of 52 students. Data were analyzed using simple regression test and t-test. The results showed that there was an effect of card sort media and couple cards on the critical thinking skills of IPAS fourth grade students of SD Negeri 1 Margajaya in the 2023/2024 academic year and there were differences in IPAS critical thinking skills between experimental classes with card sort media which had a higher effect than the control class using couple card media so that card sort media and couple cards can be used as an alternative learning model that can improve students' critical thinking skills.